Natural compounds targeting glycolysis as promising therapeutics for gastric cancer: A review - Zhao, Maoyuan; Wei, Feng; Sun, Guangwei; Wen, Yueqiang; Xiang, Juyi; Su, Fangting; Zhan, Lu; Nian, Qing; Chen, Yu; Zeng, Jinhao (Frontiers in Pharmacology, 2022)
Gastric cancer, a common malignant disease, seriously endangers human health and life. The high mortality rate due to gastric cancer can be attributed to a lack of effective therapeutic drugs. Cancer cells utilize the glycolytic pathway to produce energy even under aerobic conditions, commonly referred to as the Warburg effect, which is a characteristic of gastric cancer. The identification of new targets based on the glycolytic pathway for the treatment of gastric cancer is a viable option, and accumulating evidence has shown that phytochemicals have extensive anti-glycolytic properties. We reviewed the effects and mechanisms of action of phytochemicals on aerobic glycolysis in gastric cancer cells. Phytochemicals can effectively inhibit aerobic glycolysis in gastric cancer cells, suppress cell proliferation and migration, and promote apoptosis, via the PI3K/Akt, c-Myc, p53, and other signaling pathways. These pathways affect the expressions of HIF-1α, HK2, LDH, and other glycolysis-related proteins. This review further assesses the potential of using plant-derived compounds for the treatment of gastric cancer and sheds insight into the development of new drugs.